Lactic acid production from Microwave-alkali pre-treated empty fruit bunches fibre using Rhizopus oryzae pellet - Hamzah, F. (Asian Network for Scientific Information, 2009)
Microwave-alkali (MW-A) pre-treated EFB consisting of 74% cellulose, 16% hemicellulose and 8% lignin was subjected to Simultaneous Saccharification and Fermentation (SSF) of lactic acid using Rhizopus oryzae NRRL 395. Two different morphologies of Rhizopus were studied for SSF of lactic acids; i.e., the clump and pellet form. Aspect Ratio (AR) was introduced to classify the pellet morphology, since cultivation of Rhizopus sp. produced non-uniform size pellets. Pellet with AR = 1 indicated a perfect pellet, while AR = 1.5 represented an ellipsoidal pellet. The AR of Rhizopus pellet used in the SSF was controlled to 1. The results showed that lactic acid production from MW-A pre-treated EFB using pellet exhibits higher lactate yield as compared to the clump Rhizopus. The lactate yield was 0.77 g g-1 EFB used after 96 h cultivation. Meanwhile, productivity of the lactic acid obtained from SSF of MW-A pre-treated EFB using pellet (AR = 1), clump (AR = 1.5) and pellet (AR = 1.5) Rhizopus oryzae NRRL 395 were 0.12, 0.089, 0.099 g L-1, respectively.